Pedagogical Counseling and language teaching of adolescents with ASD in modern Greece - Kotsi, Despina (Technium Education and Humanities, 2025)
Autism spectrum disorder (ASD) as a lifelong neurodevelopmental disorder puts a significant strain on the family. During secondary education, when the brain is rewired, language learning becomes a challenge for ASD students and their parents. Using this as a foundation, this article’s main objective is to know the vision that parents with adolescents with ASD have of the use of Pedagogical Counseling (PC) in their adolescents’ language teaching of the Greek language. Through a descriptive qualitative study, with a semi-structured interview of 16 items (n=30 parents) and an in-depth analysis, this goal has been accomplished. The main conclusion that has been reached is that participants-parents of adolescents with ASD applaud the implementation of PC for their ASD adolescents’ language learning, leading them to better linguistic competencies. Accordingly, parents will need a constant provision of PC from public schools and the Greek State, without costs and a sufficient availability of specialized staff and resources to manage their adolescents’ language learning process with greater ease and flexibility. Keywords: Pedagogical Counseling, Autism Spectrum Disorders, Teaching of the Greek language, Adolescents, Parents.